2020
DOI: 10.1080/17518423.2020.1770354
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Feeding and Gastrointestinal Symptoms, Challenging Behavior, Sensory Issues, Adaptive Functioning and Quality of Life in Children and Adolescents with Autism Spectrum Disorder

Abstract: Aim: Children and adolescents diagnosed with an autism spectrum disorder (ASD) often demonstrate difficulties with feeding. The goal of the current study was to investigate co-occurring issues that often accompany feeding problems in 120 children and adolescents with ASD.Method: This study investigated the relationship between feeding problems and gastrointestinal symptoms, challenging behavior and sensory issues, quality of life, adaptive functioning and use of complementary and alternative medicine (CAM). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…Studies vary regarding the proportion of children with ASD in samples reported to experience at least one GIS. The prevalence of GIS in autistic samples has been reported to be 30–37.4% [ 30 , 59 ] and 82.4% in the previous three months [ 41 ]. Whereas Khalil et al [ 40 ] reported that all their autistic sample ( n = 58) had at least one GIS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies vary regarding the proportion of children with ASD in samples reported to experience at least one GIS. The prevalence of GIS in autistic samples has been reported to be 30–37.4% [ 30 , 59 ] and 82.4% in the previous three months [ 41 ]. Whereas Khalil et al [ 40 ] reported that all their autistic sample ( n = 58) had at least one GIS.…”
Section: Resultsmentioning
confidence: 99%
“…The evidence regarding the prevalence of GIS affecting the upper GI tract reveals that reflux was found in 5.5% of participants [ 46 ], but in half of a sample of children with ASD ( n = 18) who had experienced reflux, this symptom had resolved in children aged 25–98 months [ 8 ]. Nausea was reported in 23.2% [ 14 ] and 27.9% [ 41 ] of the samples. Whereas vomiting was reported in between 4.2% and 11.4% of the samples [ 46 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptive behavior refers to the ability to perform the daily activities required for individual and social sufficiency ( 15 ), and is measured by the extent to which an individual can independently demonstrate developmentally appropriate practical skills, conceptual skills, and social skills ( 16 ). A cross-sectional study demonstrated that children and adolescents with ASD showed lower levels of overall adaptive functioning, as scored by the Vineland Adaptive Behavior Scale (VABS) ( 17 ). Individuals with ADHD also exhibit reduced adaptive functioning relative to their intelligence quotients (IQ)–matched typically developing (TD) group ( 18 ).…”
Section: Introductionmentioning
confidence: 99%